The Power of (No) Recognition: Experimental Evidence from the University Classroom - Nicky Hoogveld; Nikolay Zubanov (Institute for the Study of Labor (IZA), 2014)
We study the effect of recognition on performance with a field experiment involving first-year undergraduate students at a Dutch university. Our treatment, given unannounced in randomly selected student groups, was to publicly recognize students who scored within the top 30% of their group on the first of the two midterm exams. The overall treatment effect on the second midterm grade is 0.03s (s = the grade's standard deviation) for the recipients of recognition, and 0.15s for the non-recipients, both statistically insignificant. The effect for the non-recipients increases with class attendance (itself unaffected), and decreases with the distance to the cutoff grade for recognition, reaching a significant 0.44s for those exceeding the minimum attendance requirement and staying within the first quartile of the distance to cutoff. We argue that conformance to performance norm is the most likely behavioral mechanism behind our findings.
Keywords: C93; M52; 330; recognition; performance; experiment